Peramalan Harga Emas Indonesia Menggunakan Metode ARIMA - Maharani, Inayah Aulia (Universitas Multi Data Palembang, 2024)
Gold is a precious metal with a high demand from the public. High demand causes the price of gold to fluctuate and be uncertain, so predictions are needed to know the state of the market price. This research will focus on forecasting the price of Indonesian gold through the ARIMA (Autoregressive Integrated Moving Average) approach. This study uses Indonesian gold price data in the form of time series from January 2014 to December 2023 with 3652 data. The smallest AIC value, 71827.3, makes ARIMA (0,1,2) the best model. The best scenario was found with testing data of 15% with MAE of 6990.226, RMSE of 8272.612, and MAPE of 0.62%. The prediction results show that gold prices are constantly increasing, with the highest price on the 31st day reaching Rp1,138,078.